Long‐term longitudinal changes in axial length in the Caucasian myopic and hyperopic population with a phakic intraocular lens. Issue 4 (29th October 2020) - Gaurisankar, Zoraida S.; van Rijn, Gwyneth A.; Haasnoot, Geert W.; Verhoeven, Virginie J. M.; Klaver, Caroline C. W.; Luyten, Gregorius P. M.; Beenakker, Jan‐Willem M.
Abstract: Purpose: To determine the long‐term longitudinal axial length changes in myopic and hyperopic adults with an iris‐fixated phakic intraocular lens (pIOL). Methods: The medical records of patients aged ≥18 years with myopia or hyperopia who were treated with pIOL implantation between 1996 and 2011 for refractive correction with a minimum follow‐up of 5 years after pIOL implantation were analyzed. The main outcome measure was change in ocular axial length over time. Results: 149 eyes of 149 myopic patients and 27 hyperopic eyes of 27 patients were included in this study. Mean patient age was 37.1 ± 10.4 years (35% male) in the myopic group and 39.4 ± 9.4 years (4% male) in the hyperopic group. The eyes of the myopic patients showed a significant mean increase in axial length of 0.45 ± 0.61 mm after a mean follow‐up time of 144 ± 38 months (p < 0.001). In 26 eyes (17%), the axial length had increased by ≥1 mm. The mean annual axial length increase was 0.04 ± 0.06 mm. Axial elongation was associated with a higher degree of myopia (p < 0.001) and younger age (p = 0.02). The eyes of the hyperopic patients showed no change in axial length over time. Conclusions: Myopic eyes corrected with an iris‐fixated pIOL show continuous increase in axial length at an adult age. Although this study is limited to subjects with a pIOL, this is the first time myopization in Caucasian adults has been reported in a large long‐term longitudinal study.